Pengaruh Corporate Governance Terhadap Green Banking Disclosure Index Di Perbankan Syariah Periode 2016-2019 Studi Kasus : Bank Mandiri Syariah, Bank Bni Syariah, Bank Bca Syariah, Bank Bri Syariah, Bank Mega Syariah Dan Bank Muamalat - Cupian Cupian; Fakhri Afif Mulyana; Sarah Annisa Noven (ITB AAS INDONESIA Surakarta, 2023)
Many parties have expressed concern about environmental sustainability in recent years, both on a national and international scale. Governments, regulators, companies and also people around the world understand the importance of being aware of environmental issues. As a business actor, the banking sector is a sector that has an implicit impact on the environment. The banking sector is one of the main sectors that provides financing for many industries and companies. Therefore, it is the responsibility of the banking sector to ensure that stakeholders who receive bank financing, in carrying out their business activities, do not have a negative or even damaging impact on the environment. In addition, the role of good corporate governance is critical to the performance of green banking itself. This study aims to see the effect of corporate governance on the disclosure of green banking in Islamic banking in Indonesia for the 2016-2019 period. The data used are secondary data by collecting information from bank annual reports and bank sustainability annual reports. Analysis method used common effect model. The results show that the number of boards, sharia superviory boards simultaneously give a significant influence on the GDBI.